Optical absorption of metal nanoparticle arrays - Pang,JS; Xie,F; Centeno,A; Petrov,PK; Ryan,MP; Alford,N (2012)
A study into the enhanced optical absorption due to metal nanoparticle arrays fabricated by nanosphere lithography. Prediction and measurement has been undertaken. Implementation to improve the efficiency of PV solar cells is discussed. © 2012 OSA.